2021
DOI: 10.46557/001c.25733
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Digitalization and Energy Intensity: Evidence From China’s Manufacturing Sector

Abstract: The Chinese manufacturing sector has undergone an accelerated digital transformation. This study examines the impact of industrial digitalization on energy intensity in China. Energy intensity is negatively correlated with digitalization in terms of time trends, cross-sectional differences, and correlation coefficients. Our empirical analysis shows that industrial digitalization significantly increases the energy intensity of the manufacturing sector. With digital transformation, energy intensity first increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Additionally, they identify a significant positive correlation between digital capital intensity and energy intensity. Lan and Wen [142] showed that the industrial digitalization of the manufacturing sector leads to a notable increase in energy intensity. Throughout the process of digital transformation, there is an initial increase followed by a subsequent decrease, forming an inverted U-shaped relationship.…”
Section: Relationship Between Digitalization and Energy Intensitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they identify a significant positive correlation between digital capital intensity and energy intensity. Lan and Wen [142] showed that the industrial digitalization of the manufacturing sector leads to a notable increase in energy intensity. Throughout the process of digital transformation, there is an initial increase followed by a subsequent decrease, forming an inverted U-shaped relationship.…”
Section: Relationship Between Digitalization and Energy Intensitymentioning
confidence: 99%
“…Throughout the process of digital transformation, there is an initial increase followed by a subsequent decrease, forming an inverted U-shaped relationship. As of 2019, more than 80% of industries exhibited a level of digitalization below the inflection point [142].…”
Section: Relationship Between Digitalization and Energy Intensitymentioning
confidence: 99%
“…The concept of corporate sustainability pertains to an organization's capacity to fulfill its stakeholders' expectations while concurrently advancing and maintaining development throughout its existence [6]. Researchers have suggested several factors that may contribute to sustainable performance, such as organizations [7], technology [8], intellectual property [9], human resource management [10], knowledge sharing [11], lean procedures [12], corporate culture [13], and others. These factors' significant impact on sustained efficiency justifies their elevated designation as critical performance indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature has confirmed that intelligence has an important role in the labor force, especially in terms of labor substitution and polarization (Acemoglu & Autor, 2011;Autor et al, 2006;Autor & Salomons, 2018). Intelligence also has a positive role in energy saving, at the same time (Hao & Wu, 2021;Lan & Wen, 2021). Nevertheless, only a few studies have explored the impact of intelligence on TFP.…”
Section: Introductionmentioning
confidence: 99%